Volatile bodies: toward a corporeal feminism - Grosz, E. A. (Indiana University Press, 1994)
Volatile Bodies demonstrates that the sexually specific body is socially constructed: biology or nature is not opposed to or in conflict with culture. Human biology is inherently social and has no pure or natural "origin" outside of culture. Being the raw material of social and cultural organization, it is "incomplete" and thus subject to the endless rewriting and social inscription that constitute all sign systems. Examining the theories of Freud, Lacan, Merleau-Ponty, Foucault, Deleuze, Derrida, etc. on the subject of the body, Elizabeth Grosz concludes that the body they theorize is male. These thinkers are not providing an account of "human" corporeality but of male corporeality. Grosz then turns to corporeal experiences unique to women–menstruation, pregnancy, childbirth, lactation, menopause. Her examination of female experience lays the groundwork for developing theories of sexed corporeality rather than merely rectifying flawed models of male theorists.
Section: xvi, 250 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; lit4700; premier cycle; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

L'énigme de la femme : la femme dans les textes de Freud - Kofman, Sarah (Librairie générale française, 1994)
Freud devant l'énigme de la femme. Ombres et mystères. Questions et suggestions. A partir d'une minutieuse exploration de l'ensemble des textes freudiens, Sarah Kofman souligne les ambiguïtés du fondateur de la psychanalyse quand il aborde le problème de la féminité. Et notamment l'étrangeté de son attitude, faite d'atermoiements et de résistances, où l'embarras et l'inquiétude semblent finalement l'emporter sur l'esprit de rigueur dont il se réclamait. Au bout du compte, explique Sarah Kofman, les réponses données par Freud relèvent de la spéculation. Plus que des réponses, même, ce sont des solutions-écran qui servent de couverture à ce qui ne saurait être regardé en face : le sexe de la femme, de la mère. La fameuse envie du pénis, cette " idée fixe " de Freud, est l'une des pseudo-solutions, destinée à fixer la femme dans une position immuable, à maîtriser son caractère, son instabilité, sa mobilité qui la rendent inaccessible, effrayante, énigmatique : " criminelle " aux yeux des hommes. L'Enigme de la femme ou la psychanalyse revisitée.
Première publication: 1980
Keywords: 1900-1999; approches et analyses; cours; discipline; discours dominant; europe; fem1000; france; patriarcat; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences; sciences humaines; systèmes d'oppressions